2006
DOI: 10.1074/jbc.m601552200
|View full text |Cite
|
Sign up to set email alerts
|

No Change in Glomerular Heparan Sulfate Structure in Early Human and Experimental Diabetic Nephropathy

Abstract: Heparan sulfate (HS) proteoglycans are major anionic glycoconjugates of the glomerular basement membrane and are thought to contribute to the permeability properties of the glomerular capillary wall. In this study we evaluated whether the development of (micro)albuminuria in early human and experimental diabetic nephropathy is related to changes in glomerular HS expression or structure. Using a panel of recently characterized antibodies, glomerular HS expression was studied in kidney biopsies of type I diabeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 48 publications
(54 reference statements)
2
34
1
Order By: Relevance
“…51,52 Although these studies support the theory that reductions in GBM-HS contribute directly to loss of barrier function, labeling with mAb JM-403 was recently reported to be normal in diabetic humans and rats with microalbuminuria, and it was concluded that loss of GBM-HS may be a secondary event that occurs in advanced disease. 53 Here, immunostaining with both antibodies revealed that adult conditional mutants lack GBM-HS. This confirms that mouse agrin exists as a HSPG in vivo but questions the importance of GBM-HS for kidney function.…”
Section: Discussionmentioning
confidence: 76%
“…51,52 Although these studies support the theory that reductions in GBM-HS contribute directly to loss of barrier function, labeling with mAb JM-403 was recently reported to be normal in diabetic humans and rats with microalbuminuria, and it was concluded that loss of GBM-HS may be a secondary event that occurs in advanced disease. 53 Here, immunostaining with both antibodies revealed that adult conditional mutants lack GBM-HS. This confirms that mouse agrin exists as a HSPG in vivo but questions the importance of GBM-HS for kidney function.…”
Section: Discussionmentioning
confidence: 76%
“…Furthermore, although the enzyme heparanase was found to be increased in STZ-induced diabetic rats, this was actually not found to imply a significant reduction in the GBM HS content (37). Furthermore, no change in HS sulfation or charge density has been detected in early STZ-induced diabetes (35). Hence, the contribution of a decreased charge selectivity in the urinary hyperexcretion of albumin in early DNP is controversial.…”
Section: Discussionmentioning
confidence: 92%
“…However, several recent studies suggest that heparan sulphate in the GBM may not play a primary decisive role in the chargeselective permeability properties and development of proteinuria. For example, van den Born recently reported that there was no change in glomerular heparan sulphate content in early human and experimental diabetic nephropathy, although in both cases albuminuria was present [15]. Additional studies have shown that rats did not develop acute albuminuria after in vivo degradation of heparan sulphate by heparinase III [35].…”
Section: Discussionmentioning
confidence: 99%
“…Production of the core protein of agrin, the major heparan sulphate proteoglycan in the GBM, was not aberrant [11,13]. However, these heparan sulphate changes occur at the macroalbuminuric stage of diabetic nephropathy, since no glomerular heparan sulphate alterations were found at the microalbuminuric stage [15]. Recently, we showed that glomerular production of heparanase, an endo-β-1,4-D-glucuronidase involved in the hydrolytic cleavage of the β-1,4-glycosidic bond between glucuronic acid and glucosamine residues within N-sulphated and/or Nacetylated/N-sulphated domains of heparan sulphate [16,17], was increased in patients with overt diabetic nephropathy [11,18].…”
Section: Introductionmentioning
confidence: 87%